Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai PT. Telkom Prima Cipta Certifia - Hani Hatimatunnisani; Mira Veranita; Dwi Robiul Rochmawati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This study intends to explain the effect of work motivation on employee performance at PT. Telkom Prima Cipta Certifia. Respondents as many as 55 employees were taken as samples for data collection through questionnaires. The results of the analysis show that there is a strong and significant relationship between work motivation and employee performance, namely 55.9% of the employee performance variance is influenced by work motivation, and the remaining 44.1% is influenced by other factors outside the variables studied.